#### Answer

$3sin (x^{2}) -2 $

#### Work Step by Step

$f(g(h(x)))=f(g(x^{2}))=f(sin (x^{2})) =3sin (x^{2}) -2 $

Published by
Cengage

ISBN 10:
1285740629

ISBN 13:
978-1-28574-062-1

$3sin (x^{2}) -2 $

$f(g(h(x)))=f(g(x^{2}))=f(sin (x^{2})) =3sin (x^{2}) -2 $

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.